2023
DOI: 10.30994/jceh.v6i1.432
|View full text |Cite
|
Sign up to set email alerts
|

Pelatihan Pembuatan Handsanitizer berbasis Ekoenzim dari Limbah Organik Buah-Buahan

Abstract: Handsanitizer adalah produk antiseptik tangan yang pemakaiannya praktis. Produk ini semakin popular penggunaannya selama berlangsungnya pandemi Covid 19. Pada umumnya, produk ini mengandung alkohol sebagai bahan antiseptik utamanya, sehingga jika pemakaian dalam jangka waktu lama dengan intensitas yang tinggi akan menyebabkan iritasi, kekeringan kulit dan terkikisnya lapisan sebum pelindung kulit. Hal ini menyebabkan pentingnya bahan antiseptik alami yang memiliki aktivitas antimikroba tetapi sifat iritasinya … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…are found in the Waters of East Asia to Southeast Asia [2], The presence of sea cucumbers Acaudina sp. are located in the Paloh Waters, Sambas Regency, West Kalimantan, Delta Wulan Waters, Kenjeran Waters (Surabaya) [3,10,14], Although in the Delta Wulan Waters, Demak areas, Acaudina sp. do not eaten by the community.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…are found in the Waters of East Asia to Southeast Asia [2], The presence of sea cucumbers Acaudina sp. are located in the Paloh Waters, Sambas Regency, West Kalimantan, Delta Wulan Waters, Kenjeran Waters (Surabaya) [3,10,14], Although in the Delta Wulan Waters, Demak areas, Acaudina sp. do not eaten by the community.…”
Section: Introductionmentioning
confidence: 99%
“…has an important role in the benthic ecosystems such as enhancing redox potential in sediment, increasing mineralization and nutrient cycling in sediment subtrate [4,5,10]. Additionally, A. molpadiodes from Paloh Waters, West Kalimantan contains relatively high protein, an essential mineral, and fucoidan [3,17,18] Furthermore, A molpadiodes from Riau Archipelago Waters showed that there was antibacterial activity toward Staphylococcus aureus, and Escherichia coli [13,19].…”
Section: Introductionmentioning
confidence: 99%